The Association of Persistent Low Back Pain With Older Adult Falls and Collisions: A Longitudinal Analysis. (November 2021) - Bell, Tyler; Pope, Caitlin; Fazeli, Pariya; Crowe, Michael; Ball, Karlene
Mobility-related injuries associate with reduced quality of life, greater functional dependence, and quicker mortality in older adults—warranting prevention efforts. One factor elevating injury risk may be persistent low back pain, which can negatively affect cognitive and physical functions essential for safe mobility. Among older adults obtaining license renewal ( n = 1, 127), this study examined the association between persistent low back pain and incidence of falls and motor vehicle collisions (MVCs) for up to 15 years. Overall, older adults with persistent low back pain were more likely to have a fall (odds ratio [OR] = 1.54, 95% confidence interval [CI] = [1.34, 1.77]) or MVC (OR = 1.38, 95% CI = [1.07, 1.77]) than those without back pain. Furthermore, the number of falls and MVCs was lower for people with better lower limb and visuospatial function, respectively. Ameliorating pain and functioning in persistent lower back pain might contribute to improved mobility and a reduction of injury-related risk in later life.